A LEARNING MODEL OF BAHASA INDONESIA AS A FOREIGN LANGUAGE BASED ON LOCAL INTERCULTURAL POLITENESS - Gusnawaty Gusnawaty; Andi Nurwati (LPMPP Universitas Negeri Yogyakarta, 2019)
The study was aimed for developing a learning model of Bahasa Indonesia based on local intercultural politeness to improve the foreigners’ communicative competencies. This is Research and Development, started with a preliminary study of intercultural learning concepts and Buginese politeness strategies; the distribution of the needs analysis instruments to the 25 foreigners learning Bahasa Indonesia in Makassar, South Sulawesi, Indonesia; model development, focus group discussions; the model finalization and product experiment. The interviews and questionnaires data were analyzed by descriptive quantitative and qualitative. The result, a local politeness intercultural learning model consisting of four phases: noticing, comparing, reflecting, and interacting. 1) The foreign learners noticed the use of local politeness markers in Bahasa Indonesia; 2) They compared the similarities and differences between the use of the markers of local politeness and those they found in their native languages; 3) They reflected themselves; 4) They practiced Bahasa Indonesia through direct interactions. The conclusion showed that the t-score = 3.26 t-table = 2.45 signifying that the model was effective in overcoming the foreign learners’ problems in oral interactions and improving their Bahasa Indonesia communicative competencies.